Exploration of natural microflora from stingless bee honey harvested from Limau Manis area, Padang, West Sumatra, Indonesia - NURMIATI NURMIATI; HENNY HERWINA; PERIADNADI PERIADNADI; MUHAMMAD NAZRI JANRA; RANTI HIDAYAT; TRI WIDYA EDELWIS (Society for Indonesian Biodiversity, 2024)
Abstract. Nurmiati N, Herwina H, Periadnadi P, Janra MN, Hidayat R, Edelwis TW. 2024. Exploration of natural microflora from stingless bee honey harvested from Limau Manis area, Padang, West Sumatra, Indonesia. Biodiversitas 25: 2908-2916. The natural microflora in stingless bee honey has been explored in three stingless bee species: Tetragonula laeviceps Smith, 1857; Heterotrigona itama Cockerell, 1918; and Geniotrigona thoracica Smith, 1857. This study aimed to identify and analyze the proportions of natural microflora in stingless bee honey. The study used a survey method, with data being descriptively analyzed and presented. The focus was on identifying microflora groups of bacteria and yeast in the honey from these three stingless bee species. Proteolytic bacteria Microflora types were identified based on the medium used: GPA+CaCO3 for acidic microbes, SMA for proteolytic bacteria, and ethanol+CaCO3 for acetic acid microbes. The pour plate method was used to count the microbes. T. laeviceps honey (pH 3.3, sugar level 45% Brix) contained a total of 163.6×104 CFU/mL microflora (161.6×104 CFU/mL bacteria and 2×104 CFU/mL yeast). In contrast, honey from H. itama (pH 3.4, sugar level 57% Brix) harbored a total of 156.7 x 104 CFU/mL microflora (155.7×104 CFU/mL bacteria and 1×104 CFU/mL yeast) and G. thoracica honey (pH 3.7, sugar level 70% Brix) contained 129.6×104 CFU/mL bacteria only. Acidic (A) and proteolytic (P) bacteria were observed in honey samples from T. laeviceps (A= 69.3×104 CFU/mL; P= 36×104 CFU/mL), G. thoracica (A= 53.6×104 CFU/mL; P= 40×104 CFU/mL), and H. itama (A= 67.0×104 CFU/mL; P= 38.6×104 CFU/mL). Acidic and proteolytic bacteria were present in all three honey samples. In conclusion, the microflora composition in stingless bee honey varies across species, with bacteria being the dominant group in all samples. The pH and sugar content of honey may influence the microbial load, indicating a possible link between honey properties and microbial diversity.